(untitled) (London Journal of Engineering Research, 2023)
The present investigation was based on analyzingthe signal generated by the electromagnetic spectrum displayequipmentSAG4400L-NWT4000. Taking in to accountan operating range of 850-1900 MHz of a mobile operator. With the use of this device, it was possible to compare the the or eticalvs. experimental postulates obtained through the tests carriedoutinthisstudy.